Distillation of power in Don Delillo's White Noise - Babaee, Ruzbeh; Siva, Shivani (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
In spite of declaring that he did not understand the meaning of postmodernism, Michel Foucault is now largely recognized as one of the pioneers of the postmodern school. It is said that Foucault represents both radical epistemological ‘decenterings’ of knowledge and truth (Harrison, 1992:84), while he suggests a somehow structuralist view of the influences of discourse, knowledge, and power on society. Foucault states that, through discourse, power is scattered, and power conflicts can take place at many various places and levels. The present paper is an analysis of Foucault’s central concepts of discourse, knowledge/power, and truth in Don Delillo’s White Noise (1985) where Delillo states “Knowledge changes every day.” (White Noise, 321).